Growth and production of Melia dubia under silvi-pasture systems and sole plantations: positive implications of intercropping hybrid napier - Prajapati, D R; Thakur, Narender Singh; Gunaga, R P; Bhuva, D C (Indian Journal of Agroforestry, 2023)
Growth and yield performance of Melia dubia was evaluated under silvi-pasture systems [M. dubia- Hybrid napier (HN)] and sole plantations, to ascertain effect of intercropping HN for two years. The study was comprised of ten treatments: land uses- LU1 to LU5 [M. dubia (2 × 2 or 3 × 3 or 3 × 2 or 4 × 4 or 4×2 m) + HN] and LU6 to LU10 sole M. dubia with same spacing) with four replications following Randomized Block Design. Results revealed that, at planting (January, 2018) and final HN forage harvest (December, 2019), significantly (p